KESESUAIAN PENDIDIKAN ISLAM DENGAN KEARIFAN LOKAL DI MIN 2 KUBU RAYA - SOLIHIN, SOLIHIN (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
Instilling the values ​​of local wisdom-based religious education is an effective effort to counteract the degradation of religious values ​​in students in the digital era. This study aims to determine the strategies that have been implemented by MIN 2 Kubu Raya in instilling the values ​​of local wisdom-based Islamic education. This research is a qualitative descriptive research. Data collection was carried out through structured and unstructured interviews, observation, and documentation. The data analysis was carried out through the stages of data reduction, data presentation and verification. The results of this study indicate that in instilling the values ​​of Islamic education based on local wisdom, MIN 2 Kubu Raya has implemented a strategy of cultivating religious values ​​through activities based on local wisdom such as tahlilan, grave pilgrimage, silaturrahim and halalbihalal. The values ​​of Islamic education that have been instilled are in the form of aqidah values, namely faith in Allah and in the Last Day; moral values, namely compassion, social care, politeness, and devotion to parents and teachers; and the value of worship in the form of reciting dhikr of the holy verses of the Qur'an and the sentence of thayyibah.